Dehydrogenation of Dodecahydro‐N‐ethylcarbazole on Pt(111). Issue 6 (14th May 2013) - Gleichweit, Christoph; Amende, Max; Schernich, Stefan; Zhao, Wei; Lorenz, Michael P. A.; Höfert, Oliver; Brückner, Nicole; Wasserscheid, Peter; Libuda, Jörg; Steinrück, Hans‐Peter; Papp, Christian
<x xml:space="preserve">Abstract</x> Sloshing hydrogen: Liquid organic hydrogen carriers are high‐boiling organic molecules, which can be reversibly hydrogenated and dehydrogenated in catalytic processes and are, therefore, a promising chemical hydrogen storage material. One of the promising candidates is the pair N‐ethylcarbazole/perhydro‐N‐ethylcarbazole (NEC/H12‐NEC). The dehydrogenation and possible side reactions on a Pt(111) surface are evaluated in unprecedented detail.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>